Merariq Adat as means to end Child Marriage: Rights and Vulnerability of Girls - Iklilah Muzayyanah Dini Fajriyah (Jurnal Perempuan, 2016)
This paper elaborates strategy to stop child marriage in NTB (Nusa Tenggara Barat) via local culture that internalized in formal education. Child marriage has ruined the future of children. This practice is not just as well as ignoring the rights of children under the disguise of religion and adat. Child marriage in NTB via merariq tradition has violated child’s rights as well as making girls vulnerable under Sasak Adat Law. However if being investigated further this tradition is giving full autonomy to girls in taking decision in marriage. In modern era, this rights and autonomy are not being exercised and even erased from girls’s rights. this creates more vulnerability to girls. The reformed merariq adat law need to be reformed and inserted into formal education so that girls are empowered and able to fight against child marriage.